2016
DOI: 10.1253/circj.cj-16-0106
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Global Strain for Estimating Relaxation and Filling Pressure – A Multicenter Study –

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp that these parameters do not necessarily correlate with invasively measured LV filling pressure in patients with hypertrophic cardiomyopathy, 2 severely reduced LV systolic function, 3 and heart failure with preserved ejection fraction (EF). 4 Editorial p 1104Reasons for inaccuracies with tissue Doppler-derived parameters could include angle dependency and myocardial tethering, levated left ventricular (LV) fillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 31 publications
4
33
0
4
Order By: Relevance
“…8 The present study further elucidated that (1) the coincidence of hypertension and LVEF Abbreviations as in Tables 1-3.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…8 The present study further elucidated that (1) the coincidence of hypertension and LVEF Abbreviations as in Tables 1-3.…”
Section: Discussionsupporting
confidence: 66%
“…15 However, the SMAP study, which we conducted in clinical patients referred for cardiac catheterization, showed that e′ significantly but only weakly correlated with τ. 8 In the present analysis, we tested the determinants of e′ to clarify the factors other than τ that influence e′ because the characteristics of the studied patients could have altered the relationship between τ and e′. As a result, we found that hypertension as a comorbidity and LVEF, but not τ, were the determinants of e′.…”
Section: Determinants Of E′mentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, Hayashi et al. demonstrated in their prospective multicenter study that left ventricular global longitudinal strain (LVGLS) derived from 2D speckle tracking was correlated better with the time constant of LV pressure decay (τ) than E′, and E to LVGLS ratio (E/LVGLS) had a better correlation to LV mean diastolic pressure than E/E′ . These findings suggested that LVGLS was not the only utilized for the evaluation of LV systolic function, but also LV diastolic function.…”
Section: Introductionmentioning
confidence: 99%